THE EFFECT OF USING MNEMONIC METHOD ON TEACHING VOCABULARY MASTERY AT THE SEVENTH GRADE STUDENTS’ OF SMP NEGERI 22 BUTON TENGAH - Salfiani, Salfiani; Nggawu, La Ode; Agustina, Sitti (Journal of Teaching of English, 2020)
This research was conducted to find out whether there was a significant effect of the Mnemonic method in teaching vocabulary mastery at the Seventh-grade students’ of SMPN 22 Buton Tengah. The design of the research was a pre-experimental design ( one group pre-test post-test design). The population of this research was the seventh-grade (VII) of SMPN 22 Buton Tengah which consists of three classes, while the sample in this research was class VII3 that consisted of 25 students and used a simple random sampling technique. The instrument in this study was multiple choices, matching tests and public buildings, food, people around us to the topic. This study was conducted three sections namely pre-test, treatment, and post-test. The researcher used a paired sample T-test through SPSS 16.0 version to analyze the result of this research. The result showed that the mean score of students’ vocabulary mastery in the post-test was higher than students’ vocabulary in the pre-test ( 53.6 > 45.28 ). The hypothesis testing found that the value of sig ( 2 Tailed ) was 0.00 while the significant alpha value was 0.05. It can be concluded that the value of Sig ( 2 Tailed) was lower than the significance of α value (0.000< 0.05). in other words, (H1) was accepted. It showed that there was a significant effect of using the Mnemonic Method on teaching vocabulary mastery at the seventh-grade students of SMPN 22 Buton Tengah.